Comparative dental study between Homo antecessor and Chinese Homo erectus: Nonmetric features and geometric morphometrics. Issue 161 (December 2021) - Bermúdez de Castro, José María; Xing, Song; Liu, Wu; García-Campos, Cecilia; Martín-Francés, Laura; Martínez de Pinillos, Marina; Modesto-Mata, Mario; Martinón-Torres, María
Abstract: The Chinese Middle Pleistocene fossils from Hexian, Xichuan, Yiyuan, and Zhoukoudian have been generally classified as Homo erectus s.s. These hominins share some primitive features with other Homo specimens, but they also display unique cranial and dental traits. Thus, the Chinese Middle Pleistocene hominins share with other European and Asian hominin populations the so-called 'Eurasian dental pattern'. The late Early Pleistocene hominins from Gran Dolina-TD6.2 (Spain), representing the species Homo antecessor, also exhibit the Eurasian dental pattern, which may suggest common roots. To assess phylogenetic affinities of these two taxa, we evaluated and compared nonmetric and metric dental features and interpreted morphological differences within a comparative hominin framework. We determined that the robust roots of the molars, the shelf-like protostylid, the dendrite-like pattern of the enamel-dentine junction surface of the upper fourth premolars and molars, the strongly folded dentine of the labial surface of the upper incisors, and the rare occurrence of a mid-trigonid crest in the lower molars, are all characteristic of Chinese H. erectus . With regard to H. antecessor, we observed the consistent expression of a continuous mid-trigonid crest, the absence of a cingulum in the upper canines, a complex root pattern of the lower premolars, and a rhomboidal occlusal contour and occlusal polygon and protrusion in the external outline of a large a bulging hypocone in the first and second upper molars. Using two-dimensional geometric morphometrics, we further demonstrated that H. antecessor falls outside the range of variation of Chinese H. erectus for occlusal crown outline shape, the orientation of occlusal grooves, and relative locations of anterior and posterior foveae in the P 4 s, P3 s, M 1 s, M 2 s, and M2 s. Given their geographic and temporal separation, the differences between these two species suggest their divergence occurred at some point in the Early Pleistocene, and thereafter they followed different evolutionary paths. Highlights: Comparing Homo antecessor and Chinese H. erectus, two distant taxa in space and time. Some nonmetric dental features distinguish H. antecessor from Chinese H. erectus. 2D geometric morphometrics analyses also differentiate between these two taxa.